Integration of Digital Technology in Human Resource Management: Strategies to Increase Employee Engagement in The Industry 4.0 Era - Rizqi Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Delving into the intricate relationship between digital technology and employee engagement within the dynamic context of the industry 4.0 era, this study embarks on an exploration of innovative motivation strategies. Through a meticulous examination encompassing contemporary literature and relevant case studies, it sheds light on the myriad ways organizations can harness the potential of digital tools, such as immersive learning platforms, gamified training modules, and real-time feedback mechanisms. By leveraging these technologies, organizations can create a conducive workplace environment that not only fosters intrinsic motivation but also instills a sense of purpose and facilitates ongoing professional development among employees. With a focus on providing actionable insights and showcasing effective approaches, this paper endeavors to serve as a valuable resource for organizations seeking to optimize digital technology to elevate employee engagement levels. Ultimately, by aligning digital initiatives with strategic objectives, organizations can not only enhance employee engagement but also thrive amidst the ever-evolving landscape of Industry 4.0.